If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3w + 3 = 9 Reorder the terms: 3 + 3w = 9 Solving 3 + 3w = 9 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3w = 9 + -3 Combine like terms: 3 + -3 = 0 0 + 3w = 9 + -3 3w = 9 + -3 Combine like terms: 9 + -3 = 6 3w = 6 Divide each side by '3'. w = 2 Simplifying w = 2
| 3 w+ 3= 9 | | 81u^2+36u+4=0 | | 2v+6=-4(v+3) | | x^3-3x^2-600=0 | | 4a-(2a+4)= | | v^2+14vy+49y^2=0 | | 4(6x+10)=-8(-4x+7) | | -3(x-5)=x-13 | | -(1x-2)-6.5=2.5x+19 | | 6x+17=15x-111 | | 2x+8=4(x-3) | | 2v+6=-4(1v+3) | | 4z=-40 | | x+35=84-74 | | 180-x=2(x+20) | | 180x=2(x+20) | | -5.7p+10.16=-65.08 | | x+20=180-2(x+20) | | 2[x+3]=-4[x+1] | | -3b+ax=x-4 | | x+20=180-(x+20) | | 147-3b^2=0 | | (2b^5-5b^4+8b^3-12b^2+12b-9)= | | 15y-16=7y-15 | | 0.2n+3= | | 3(2x+5)=5x+12 | | 7[3-(-4x-1)]=252x+84 | | 10x-8=102 | | 8x-2(x-5)=x+5 | | 31s+10=-14s | | V^2+12v-24=0 | | 6(2t+5)=4 |